Thailand Diabetes Registry Project: Prevalence of hypertension, treatment and control of blood pressure in hypertensive adults with type 2 diabetes - Pongamorn Bunnag (2018)
Objective: To determine the prevalence of hypertension, patterns of antihypertensive treatment and level of blood pressure control in adult Thai type 2 diabetic patients who attended diabetes clinics in university and tertiary-care hospitals. Material and Method: A cross-sectional, multi-center, hospital-based diabetes registry of 8,884 adults 18 years old and older was carried out from diabetes clinics of 11 tertiary centers. Demographic data, including use of antihypertensive drugs and blood samples were collected and analyzed for prevalence, associated factors, patterns of antihypertensive therapy and level of blood pressure control. Results: The prevalence of hypertension in adult Thai type 2 diabetic patients was 78.4 (6,965)%. Antihypertensive drugs were prescribed in 84.4 (5,878)% of all hypertensive patients. The achievement of blood pressure control (less than 130/80 mmHg) was 13.85%. The percentage of patients receiving 1, 2, 3, 4, and 5 drugs were 45 (2,645)%, 33.4 (1,963)%, 16.8 (987)%, 4.4 (259)%, and 0.4 (24)% respectively. Angiotensin-converting enzyme inhibitors were the most commonly prescribed antihypertensive agents (54.6%), followed by diuretics (43.8%), and calcium channel blockers (34.6%). Conclusion: Blood pressure control in hypertensive adults with type 2 diabetes was suboptimal. Strategies to improve awareness and adequacy of blood pressure control in these subjects should be seriously considered.